Manejo y tratamiento del tumor del seno endodérmico de ovario en adolescente de 14 años: reporte de caso - Mallqui-Mejía, Mirela A. (2023)
Malignant tumors in adolescence are rare, and they are usually of germinal origin. Specifically, endodermal sinus tumors of the ovary are exceptional in this population. In this case report, we present a 14-year-old adolescent diagnosed with this type of tumor in her right ovary at the Gynecology Service of the Instituto Nacional de Salud del Niño San Borja, Lima, Peru. This case is the first of its kind in the institution, and no similar cases have been reported in our country, underscoring its significance. The patient had a large mixed tumor of 1470 grams, detected through pelvic magnetic resonance imaging. Tumor markers allowed a presumptive diagnosis of a probably malignant ovarian tumor. As a result, the patient underwent laparotomy, unilateral salpingo-oophorectomy, frozen biopsy, and staging. Subsequently, the patient received chemotherapy with good results, and alpha-fetoprotein levels normalized during follow up.